The Influence of Guided Inquiry Model Assisted by Animation Media on Science Subjects Towards Curiosity Attitude and Mastery of Science Concepts (Universitas Negeri Semarang, 2022)
This research is based on a fairly low curiosity attitude towards conventional science learning. The renewal of student-centered learning (Guided Inquiry Model) with the help of animation media is needed to increase curiosity and mastery of science concepts. This research aims to find out the influence of guided inquiry models assisted by animation media to increase curiosity and mastery of the science concept of fifth-grade students in SDN 02 Bae Kudus. The design of this study used a quasi-experimental design to measure causal relationships using a non-equivalent control group design. The results of this study found that the average control class was 81.28 compared to the experimental class with an average score of 84.73. Meanwhile, using the t-test with paired samples test obtained mastery of the concept of control class Science of 85.3 in the experimental class with an average score of 85.3. It can be concluded that the guided inquiry model based on animation media is effective to improve students' curiosity attitudes so that students learn so that mastery of science concepts in experimental classes is better compared to in control classes. Furthermore, the average curiosity attitude score in the experimental class was 84.07 greater than in the control class of 78.00. So, it can be concluded that the guided inquiry model based on animation media affects the curiosity attitude toward learning science. Based on the simple linear regression analysis that the significance value of the curiosity attitude variable of 0.000 is smaller than 0.05, so it can be concluded that there is a correlation between curiosity attitudes to mastery of student science concepts.